Future prospects of the print newspaper in Zimbabwe. (7th October 2011) - CHARI, TENDAI
The Internet has fundamentally transformed the media landscape in Zimbabwe. The technology has spawned new practices, whose impact on the printed newspaper is dialectical. On the one hand, newspapers are able to assert their presence globally through online editions, thus improving their readership. On the other, the technology portends the demise of the printed newspaper due to competition presented by online editions. This study examines newspaper reading habits in Zimbabwe in order to ascertain the impact of the Internet on the printed newspaper. The study combines survey method and in-depth interviews, in order to gain insights into the future prospects of the printed newspaper in the Internet age in an African context. The article argues that while there is considerable interest for the Internet newspaper in Zimbabwe, the print newspaper is far from extinction. The reasons for this include the low diffusion of the Internet and a host of socio-economic and cultural factor.